2018
DOI: 10.1038/s41366-018-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Inference about causation between body mass index and DNA methylation in blood from a twin family study

Abstract: For middle-aged women, peripheral blood DNA methylation at several genomic locations is associated with current BMI, BMI at age 18-21 years and BMI change. Our study suggests that BMI has a causal effect on peripheral blood DNA methylation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…These new discoveries have important implications for understanding the causes of breast cancer. We have applied a new method for making inference about causation by examining familial confounding, called ICE FALCON [34], to data on twin pairs. We found no evidence that conventional DNA methylation in blood is having a causal effect on conventional mammographic density (Cumulus), or vice versa [35].…”
Section: Discussionmentioning
confidence: 99%
“…These new discoveries have important implications for understanding the causes of breast cancer. We have applied a new method for making inference about causation by examining familial confounding, called ICE FALCON [34], to data on twin pairs. We found no evidence that conventional DNA methylation in blood is having a causal effect on conventional mammographic density (Cumulus), or vice versa [35].…”
Section: Discussionmentioning
confidence: 99%
“…For sites affected by genetic factors, we used the methylation site heritability estimates found by van Dongen et al by analysing NTR data, 13 and the methylation quantitative trait locus (mQTL) results by Min et al 32 Loci associated with smoking or BMI included AHRR, F2RL3, 2q27.1, 6p21.33, HIF3A, SOCS3 and ABCG1. 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 DNA methylation, one of the most studied epigenetic modifications, has been found to be associated with several human traits and diseases, such as smoking 3 , 4 , 5 and obesity. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…The BMI classi cation results were found to be signi cantly associated with the presence of INS gene methylation before and after the intervention in the studied population. Previous epigenome studies have reported that there are CpG islands, approximately 500, which may be methylated in relation to the BMI [29], [30]. The causality between BMI and DNA methylation has been analyzed, suggesting that BMI and its change have a causal effect on DNA methylation [30].…”
Section: Resultsmentioning
confidence: 99%